Phenotypic vs. genetic cascade screening for familial hypercholesterolemia: A case report - Blokhina, Anastasia V.; Ershova, Alexandra I.; Meshkov, Alexey N.; Kiseleva, Anna V.; Klimushina, Marina V.; Zharikova, Anastasia A.; Sotnikova, Evgeniia A.; Ramensky, Vasily E.; Drapkina, Oxana M. (Frontiers in Cardiovascular Medicine, 2022)
One of the most common autosomal dominant disorders is familial hypercholesterolemia (FH), causing premature atherosclerotic cardiovascular diseases and a high risk of death due to lifelong exposure to elevated low-density lipoprotein cholesterol (LDL-C) levels. FH has a proven arsenal of treatments and the opportunity for genetic diagnosis. Despite this, FH remains largely underdiagnosed worldwide. Cascade screening is a cost-effective method for the identification of new patients with FH and the prevention of cardiovascular diseases. It is usually based only on clinical data. We describe a 48-year-old index patient with a very high LDL-C level without controlled guidelines-based medication, premature atherosclerosis, and a rare variant in the low-density lipoprotein receptor (LDLR) gene. Phenotypic cascade screening identified three additional FH relatives, namely the proband's daughter, and two young grandsons. The genetic screening made it possible to rule out FH in the proband's younger grandson. This clinical case demonstrates that genetic cascade screening is the most effective way of identifying new FH cases. We also first described in detail the phenotype of patients with a likely pathogenic variant LDLR-p.K223_D227dup.